Implementation of the Corporate Social Responsibility Policy: A Case Study of Holistic Area-Based Community Development of A FOODS Company - Saysaman, Watchara; Sammukkeetham, Somsak (Journal of Social Development and Management Strategy, 2021)
This research aims to study the implementation, problems, and obstacles of corporate social responsibility (CSR) policy of A FOODS company in the holistic area-based community development projects. The qualitative methodology was used and data was collected by interviewing key informants and participant observation in the CSR policy implementing department. The results found that the CSR policy of A FOODS committed to the Triple Bottom Line framework that focused on economic, social, and environment aspect. Also, it expressed that the board of directors emphasized and imposed the policy. Therefore, the corporate social contribution office was established and organized specifically as known as the CSR after process and was supported by resources including budgets and human resource. The corporate social contribution office aims to manage the holistic area-based community development projects in the manufacturing area model. The projects caused a community development involvement between company and stakeholders. However, it can be generally found that the transforming policy to programs and projects were not necessary to problems and local community niche around manufacturing areas. Especially, agricultural water resource degeneration and environmental impact from the manufacturing process.